2017
DOI: 10.1128/jvi.00357-17
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle-Dependent Expression of Adeno-Associated Virus 2 (AAV2) Rep in Coinfections with Herpes Simplex Virus 1 (HSV-1) Gives Rise to a Mosaic of Cells Replicating either AAV2 or HSV-1

Abstract: Adeno-associated virus 2 (AAV2) depends on the simultaneous presence of a helper virus such as herpes simplex virus 1 (HSV-1) for productive replication. At the same time, AAV2 efficiently blocks the replication of HSV-1, which would eventually limit its own replication by diminishing the helper virus reservoir. This discrepancy begs the question of how AAV2 and HSV-1 can coexist in a cell population. Here we show that in coinfected cultures, AAV2 DNA replication takes place almost exclusively in S/G 2 -phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 69 publications
(23 reference statements)
2
15
0
Order By: Relevance
“…During this time frame we would expect that most of the infected cell population would have reached the G 1 or the S phase, which would also be in accordance with AAV and HSV active role in modulation of the cell cycle to their benefit. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…During this time frame we would expect that most of the infected cell population would have reached the G 1 or the S phase, which would also be in accordance with AAV and HSV active role in modulation of the cell cycle to their benefit. 14 , 15 …”
Section: Discussionmentioning
confidence: 99%
“…This raises the question of how those different viruses can coexist in a cell population. AAV and HSV-1 replicate during different cell cycle phases and hence replicate in two different ecological niches [ 232 ]. In the absence of AAV, HSV-1 replication is cell-cycle independent and blocks cell cycle progression in the G1 and G2 phases [ 233 , 234 , 235 , 236 ].…”
Section: Aav-mediated Inhibition Of Helper Virus Replicationmentioning
confidence: 99%
“…In the absence of AAV, HSV-1 replication is cell-cycle independent and blocks cell cycle progression in the G1 and G2 phases [ 233 , 234 , 235 , 236 ]. AAV gene expression and replication were found to preferentially occur in S/G2 phases of the cell cycle [ 232 ]. Restriction of AAV replication and gene expression to S/G2 was not dependent on second-strand synthesis as self-complementary rAAV showed the same cell cycle preference.…”
Section: Aav-mediated Inhibition Of Helper Virus Replicationmentioning
confidence: 99%
“…30 For example, Rep78 arrests the cells in S-phase via multiple pathways, 31,32 and AAV2 genome replication occurs primarily in S/G2 phase. 33 We hypothesized SKA2 and/or ITPRIP may modulate the cell cycle in a manner that increases AAV genome replication, resulting in increased AAV titer. Flow cytometric analysis of 4 0 ,6-diamidino-2-phenylindole (DAPI) staining revealed that cell-cycle distribution was similar for normally propagating WT, SKA2-, and ITPRIP-expressing cell lines (Figure S6).…”
Section: Stable Cell Line Generation For Verification Of Grna Hitsmentioning
confidence: 99%